2022
DOI: 10.1128/spectrum.02674-21
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota of Obese Children Influences Inflammatory Mucosal Immune Pathways in the Respiratory Tract to Influenza Virus Infection: Optimization of an Ideal Duration of Microbial Colonization in a Gnotobiotic Pig Model

Abstract: The diversity of gut microbiome of obese people differs markedly from that of lean healthy individuals which, in turn, influences the severity of inflammatory diseases because of differential maturation of immune system. The mouse model provides crucial insights into the mechanism(s) regulating the immune systems mediated by the gut microbiota but its applicability to humans is questionable because immune cells in mice are poorly activated in microbiota humanized mice. Several important strains of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 87 publications
1
4
0
Order By: Relevance
“…Very little is known about how gut microbiota responds to influenza virus infection, but the observed increase in Klebsiella , whose members have polysaccharide-based capsules and colonize the nasal, oral, and intestinal tracts, concurs with a recent study that reported Klebsiella increase following influenza virus infection in piglets whose gut microbiota was humanized with fecal microbiota from healthy or obese donors [ 57 ]. Clostridium , Klebsiella , and Streptococcus all contain infectious species.…”
Section: Discussionsupporting
confidence: 72%
“…Very little is known about how gut microbiota responds to influenza virus infection, but the observed increase in Klebsiella , whose members have polysaccharide-based capsules and colonize the nasal, oral, and intestinal tracts, concurs with a recent study that reported Klebsiella increase following influenza virus infection in piglets whose gut microbiota was humanized with fecal microbiota from healthy or obese donors [ 57 ]. Clostridium , Klebsiella , and Streptococcus all contain infectious species.…”
Section: Discussionsupporting
confidence: 72%
“…Alterations in the gut microbiota are linked not only to the development of local gut pathologies, such as IBD, but are critical in systemic disorders such as obesity, dyslipidemia, hyperglycemia, and MetS. 37 , 38 Here, we add to the body of evidence showing that events occurring in the gut epithelium orchestrate systemic, microbiome-dependent consequences. Specifically, we demonstrate a direct mechanistic link between the loss of epithelial-specific DUOX2 activity and the development of MetS.…”
Section: Discussionmentioning
confidence: 94%
“…Fish infected by specific pathogens can have different gut microbial communities, which should be considered when interpreting results ( Wang C. et al, 2018 ). Several studies have evaluated host–microbe interactions by using germ-free and gnotobiotic models ( Darnaud et al, 2021 ; Pérez-Pascual et al, 2021 ; Luna et al, 2022 ; Renu et al, 2022 ), but detailed mechanisms of how the fish microbiota interact with mucosal surfaces need to be further investigated.…”
Section: Discussionmentioning
confidence: 99%